2022
DOI: 10.1186/s40359-022-00880-y
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of COVID-19-related health anxiety among health care workers: a cross-sectional study

Abstract: Background One of the psychological issues that may affect health care workers (HCWs) during the outbreak of COVID-19 is health anxiety. Health anxiety disorder goes beyond normal health concerns and can seriously affect occupational and interpersonal performance. The present study was designed to determine the level of COVID-19-related health anxiety and its predictors in Iranian HCWs. Methods This is a cross-sectional study. Data were collected o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 49 publications
(68 reference statements)
1
7
0
Order By: Relevance
“…These results are in line with other studies which indicated that problem-solving and decisionmaking skills can lead to less anxiety. 26 Furthermore, this finding is in line with other studies that emphasize the role of the family in reducing the anxiety of adolescents. [17][18] According to the family process model, healthy families are stronger in problem-solving and decision-making skills compared to unhealthy families.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…These results are in line with other studies which indicated that problem-solving and decisionmaking skills can lead to less anxiety. 26 Furthermore, this finding is in line with other studies that emphasize the role of the family in reducing the anxiety of adolescents. [17][18] According to the family process model, healthy families are stronger in problem-solving and decision-making skills compared to unhealthy families.…”
Section: Discussionsupporting
confidence: 89%
“…This scale has 38 fivepoint graded questions (strongly agree = 5 to strongly disagree = 1) which have 7 areas. 1-job and education (items 20 to 24 and 28), 2-time to spend together (items 6 to 9, 11, and 12), 3-financial resources (items 1-5), 4-physical appearance/ social status (items 13-16, 18 and 19), 5-physical and mental health (items 34-38), 6-living space (items 29-33), and 7-facilities (items [25][26][27]. The total score is obtained by summing the scores of the items.…”
Section: Self-report Family Content Scalementioning
confidence: 99%
See 1 more Smart Citation
“…The results of the study by Saeedi et al showed that employees working in health centers in Iran had high health anxiety (12). The results of the study by Benke et al indicated that individuals with high levels of health anxiety were prone to fearful mental imagery of contracting COVID-19, which might have been crucial factor contributing to the exacerbation and chronicity of excessive health anxiety in times of a pandemic (13).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, examining individual characteristics and working conditions, a correlation occurred between the number of years a healthcare worker had spent in the job, the type of the medical institute and health anxiety in such a way that the more experienced healthcare professionals working in state care showed lower health anxiety than their younger colleagues or those who worked in private care (Saeedi et al, 2022). Further results draw the attention to the influence of individual characteristics (i.e., state and trait anxiety, stress tolerance) and working conditions (i.e., social support) (Shayganfard et al, 2021).…”
Section: Literature Rewiewmentioning
confidence: 99%